Computationally-generated nuclear forensic characteristics of early production reactors with an emphasis on sensitivity and uncertainty. (December 2017) - Redd, Evan M.; Sjoden, Glenn; Erickson, Anna
Highlights: X-10 reactor is used as a case study for nuclear forensic signatures. S/U analysis is conducted to derive statistically relevant markers. Computationally-generated signatures aid with proliferation pathway identification. Highest uncertainty in total plutonium production originates from 238 Pu and 242 Pu. Abstract: With nuclear technology and analysis advancements, site access restrictions, and ban on nuclear testing, computationally-generated nuclear forensic signatures are becoming more important in gaining knowledge to a reclusive country's weapon material production capabilities. In particular, graphite-moderated reactors provide an appropriate case study for isotopics relevant in Pu production in a clandestine nuclear program due to the ease of design and low thermal output. We study the production characteristics of the X-10 reactor with a goal to develop statistically-relevant nuclear forensic signatures from early Pu production. In X-10 reactor, a flat flux gradient and low burnup produce exceptionally pure Pu as evident by the 240 Pu/ 239 Pu ratio. However, these design aspects also make determining reactor zone attribution, done with the 242 Pu/ 240 Pu ratio, uncertain. Alternatively, the same ratios produce statistically differentiable results between Manhattan Project and post-Manhattan Project reactor configurations, allowing for attribution conclusions.